Antidiabetic Activity of Manonjaya Snakefruit Skin Extract with Zebra Fish (Danio rerio) as Animal Model - Eti Rohaeti; Dea Nurafifah; Irmanida Batubara (Tropical Biopharmaca Research Center, IPB University, 2022)
This research aimed to determine the active fraction and profile of active compounds in Manonjaya sSnakefruit skin extract that can be used as antidiabetic and the antidiabetic activity using zebra fish. Manonjaya sSnakefruit skin was extracted by maceration using 70% ethanol and then fractionated using n-hexane, ethyl acetate and methanol. The ethyl acetate fraction showed the highest yield and total phenolic content as well as the strongest α-glucosidase inhibition with an inhibition percentage of 64.43%. The ethyl acetate fraction provided the most active spot as an α-glucosidase inhibitor. The profile of active compounds that act as antidiabetic compound is flavonoid from glycosylflavone and flavone groups. Antidiabetic activity using zebra fish was indicates that Manonjaya Snakefruit skin extract from ethanol extract and ethyl acetate fraction can decrease blood sugar level of zebra fish after induced with alloxan. The crude extract group had 54.51% lower sugar content than the induction group and 41.70% lower than the negative control. Meanwhile, the ethyl acetate fraction group had 65.10% lower sugar content than the induction group and 55.27% lower than the negative control.